2012
DOI: 10.1002/mabi.201100443
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Microstructured Collagen Membrane Mimicking the Papillary Dermis Architecture and Guiding Keratinocyte Morphology and Gene Expression

Abstract: A papillary-structured collagen fibril membrane is created, mimicking the 3D-architecture of the human papillary dermis. Primary human keratinocytes cultured to confluency on papillar-structured films are compared to keratinocytes cultured on flat membranes. Microscopical evaluation reveals the presence of morphologically distinct cells at the base of the papillar structures that are not observed on flat membranes. Gene expression microarrays and RT-qPCR indicate that these cells are in a more proliferative/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Later, Watt et al examined stem cell patterning in the IF epidermis by correlating the regional variation in integrin expression levels in human skin with the colony forming efficiency of keratinocytes [12, 1719]. Additionally, a recent study of keratinocytes seeded on a microfabricated dermal papilla template showed differential gene expression on micropatterned membranes compared to flat controls [27]. Given the continued lack of understanding of the role of microtopography in directing cellular phenotype, function and fate, we suggest that the topography of the dermal-epidermal junction is largely responsible for driving the clustering of these keratinocyte sub-populations and hypothesize that topographical cues can be used to direct keratinocyte phenotype and create stem cell reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Watt et al examined stem cell patterning in the IF epidermis by correlating the regional variation in integrin expression levels in human skin with the colony forming efficiency of keratinocytes [12, 1719]. Additionally, a recent study of keratinocytes seeded on a microfabricated dermal papilla template showed differential gene expression on micropatterned membranes compared to flat controls [27]. Given the continued lack of understanding of the role of microtopography in directing cellular phenotype, function and fate, we suggest that the topography of the dermal-epidermal junction is largely responsible for driving the clustering of these keratinocyte sub-populations and hypothesize that topographical cues can be used to direct keratinocyte phenotype and create stem cell reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…In the epidermis, the specific architecture of the rete ridges provides a mechanical niche for keratinocytes. This knowledge may be used in TE/RM, as in constructs with an architecture comparable to this rete ridge structure the epithelialization rate was higher than in constructs with a flat surface, and the expression of genes related to proliferation and migration was increased in keratinocytes . Mechanical strain has further been found to increase the proliferation of keratinocytes by both static and cyclic stretch, whereas differentiation was down‐regulated by static stretch .…”
Section: Mechanical Strain In Te/rm Of Orofacial Skin and Mucosamentioning
confidence: 98%
“…This knowledge may be used in TE/RM, as in constructs with an architecture comparable to this rete ridge structure the epithelialization rate was higher than in constructs with a flat surface, and the expression of genes related to proliferation and migration was increased in keratinocytes. [124][125][126] Mechanical strain has further been found to increase the proliferation of keratinocytes by both static and cyclic stretch, 38,40 whereas differentiation was down-regulated by static stretch. 40 Keratinocyte proliferation may be beneficial in the closure of wounds but can also cause a thickened epidermis as observed in hypertrophic scars and psoriasis.…”
Section: Mechanical Strain In Te/rm Of Orofacial Skin and Mucosamentioning
confidence: 99%
“…It has been widely applied in skin, nerves, heart, ocular, bone and cartilage tissue engineering [65][66][67][68].…”
Section: Tissue Regeneration and Engineeringmentioning
confidence: 99%